2019
DOI: 10.3389/fnmol.2019.00006
|View full text |Cite
|
Sign up to set email alerts
|

Schwann Cell Precursors Generate the Majority of Chromaffin Cells in Zuckerkandl Organ and Some Sympathetic Neurons in Paraganglia

Abstract: In humans, neurosecretory chromaffin cells control a number of important bodily functions, including those related to stress response. Chromaffin cells appear as a distinct cell type at the beginning of midgestation and are the main cellular source of adrenalin and noradrenalin released into the blood stream. In mammals, two different chromaffin organs emerge at a close distance to each other, the adrenal gland and Zuckerkandl organ (ZO). These two structures are found in close proximity to the kidneys and dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 49 publications
0
76
0
1
Order By: Relevance
“…Developmental differentiation of SCPs into the adrenal compartment can produce both neuroendocrine chromaffin and sympathetic neurons 9,10 . The adrenergic cells of neuroblastoma generally resembled sympathoblasts, expressing PRPH and GAP43, and lacked chromaffin markers such as PNMT (Fig 3F).…”
Section: Sox10+ Cells Expressed Erbb3 and The Ligand Nrg1 Was Expressmentioning
confidence: 99%
See 2 more Smart Citations
“…Developmental differentiation of SCPs into the adrenal compartment can produce both neuroendocrine chromaffin and sympathetic neurons 9,10 . The adrenergic cells of neuroblastoma generally resembled sympathoblasts, expressing PRPH and GAP43, and lacked chromaffin markers such as PNMT (Fig 3F).…”
Section: Sox10+ Cells Expressed Erbb3 and The Ligand Nrg1 Was Expressmentioning
confidence: 99%
“…Many tumors are known to activate and replay developmental mechanisms to attain plasticity that ultimately promotes resistance to therapy 8 . The neural crest lineage, from which neuroblastoma originates, is remarkably flexible, and can give rise to both mesenchymal and adrenergic lineages during normal development [9][10][11][12][13] . In particular, using lineage tracing experiments in mice, we have recently observed that these adrenergic and mesenchymal cell types share an immediate developmental progenitor, represented by neural crest cells diverging at last towards sympatho-adrenal and mesenchymal sub-lineages 14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2017; Kastriti et al . 2019) and that to the intrinsic neurons of the colon ~20% (Uesaka et al . 2015), we do not know at present if, and if so to what extent, SCPs contribute to the IHGCs.…”
Section: Discussionmentioning
confidence: 99%
“…2017; Kastriti et al . 2019). These two agglomerates differ in that the chromaffin cells of the adrenal medulla are positioned dorsolaterally to the coeliac plexus, whereas those of the para‐aortic bodies touch or merge in the midline (Figure A,B), with very few para‐aortic bodies found distal to the umbilical bifurcation (Coupland, 1952, Kruepunga et al ., in press).…”
Section: Discussionmentioning
confidence: 99%